Comparison of Notary Law in Indonesia and Singapore - Hussy, Maharani Millenia; Djaja, Benny (Interdisciplinary Social Studies, 2023)
Background: In order for a law to evolve, a comparative law is needed, one of which is in Notary Law. Each country has a lot of differences and of course there is a similarity in terms of Positions, Function and Regulation on how to be appointed as a Notary Public. Aim: This study examines the advantages and disadvantages by examining the similarities and differences in Terms, Functions and Position of a Notary between Act Number 2 of 2014 concerning amendments to Act Number 30 of 2004 concerning Notary Positions and the Singapore’s Notaries Public Act 1959. Method: The research method that was used in this research is normative legal research methods that focus on research in legislation, written regulations, and comparative law research. Findings: In Indonesia, notary has more functions and powers compare to Notary in Singapore. To become a Notary, a Notary must have a bachelor degree in law, a Master degree in Notary Education and Undergoes an internship or worked 24 months in a row at notary's office. Meanwhile in Singapore, Notary public is not a legal professional.